Perinatal Mental Health in Hamilton and Montreal - Ali, Shanzey; Bansal, Suraj; Durant, Ines; Reynoso, Sofia; Spector, Tiffany; Sun, Jeffrey; Zhang, Yiming (The Meducator, 2023)
Mental health concerns experienced by individuals during or up to one year after pregnancy fall under the umbrella of perinatal mental health. Estimates suggest that one in five people will experience a perinatal mental illness at some point during their pregnancy or up to one year postpartum. Racialized individuals with low socioeconomic status are at an increased risk to perinatal mental health. Perinatal mental illness is becoming an incredibly relevant topic in the sphere of public health and policy. Recently, the Canadian Task Force on Preventive Health Care released a recommendation against screening individuals for depression during pregnancy and the postpartum period (up to 1 year after childbirth), stating that there is low certainty of evidence for such screening measures. This received backlash, with groups like the Canadian Perinatal Mental Health Collaborative (CPMHC) speaking out. Prime Minister Justin Trudeau and the Minister of Mental Health and Addictions aim to “ensure timely access to perinatal mental health services”, as identified in a recent mandate letter. Given its current salience, this piece seeks to explore perinatal mental health programs in Ontario and Quebec, critically analyze their effectiveness, and suggest future areas of improvement.